Synchro destiny: harnessing the infinite power of coincidence to create miracles - Chopra, Deepak (Rider London, 2005)
Dr Deepak Chopra, the bestselling pioneer in mind/body medicine, shows how coincidences are messages about the miraculous potential of each moment. He reveals how, through understanding the forces that shape coincidences, you can learn to live at a deeper level and access the flow of synchronicity that lies at the heart of existence.